Effectiveness Of The Application Of Advocates' Immunity Rights Against The Crime Of Obstaclementation Of Investigations In Cases Of Corruption Criminal Acts Analysis of Constitutional Court Decision No. 26/PUU-XI/2013 - Endang Mulyana; Sri Hartini; Ibrahim Fajri (Universitas Ibn Khaldun Bogor, 2026)
Being an advocate is a noble profession (officium nobile), which not only has a role and function as part of law enforcement in the criminal justice system, but also dedicates its duties and responsibilities to the public interest, for the sake of upholding justice and truth, not merely for personal gain. Therefore, the Advocacy Profession must be carried out based on professionalism and in good faith, meaning carried out by prioritizing the realization of truth and justice. Although Advocates are protected by the right of immunity under Article 16 of Law No. 18 of 2003 concerning Advocates, which was later expanded by Constitutional Court Decision No. 26/PUU-XI/2013, where the right of immunity for Advocates applies in court and out of court, if an Advocate commits a violation of the law and/or commits an unethical act, neither the right of immunity nor the expanded meaning will be able to protect Advocates from legal entanglements, meaning Advocates do not have legal immunity. This research was conducted using a library research method with a normative juridical analysis approach to relevant laws and regulations with the focus of the analysis on the Constitutional Court Decision No. 26 / PUU-XI / 2013